THE BALLOTS OF YESTERYEARS: EXPLORING THE ORIGINS OF PARTY ORIENTATION AND CLASS ALIGNMENT IN VICTORIAN VOTING - Torun Tukiainen (International Journal Of History And Political Sciences, 2023)
This study examines the origins of party orientation and class alignment in Victorian voting during the 19th century. By delving into historical records, electoral data, and political discourse of the era, this research seeks to understand the factors that shaped party affiliations and class-based voting patterns. Through a comprehensive analysis of the socio-political landscape, economic conditions, and ideological shifts of the time, this study aims to shed light on the historical context that influenced the development of party orientation and class alignment in Victorian voting. The findings provide insights into the complex interplay between political ideologies, socioeconomic factors, and voter behavior, contributing to a deeper understanding of the historical roots of party politics and class-based voting patterns.